Effects of beetroot juice intake on repeated performance of competitive swimmers - Moreno, B.; Morencos, E.; Vicente-Campos, D.; Muñoz, A.; González-Gracía, J.; Veiga, S. (Frontiers in Physiology, 2023)
Background: Beetroot juice is a sport supplement with a high level of evidence on the physical performance enhancement. However, in swimming, there is no clear data about the effects of beetroot juice on performance.